(untitled) (The Pretoria Student Law Review, 2021)
International tax issues have never been at the forefront of international politics as they are today. This is due in large part to the realization that the current international tax system in existence allows multinational corporations to plan their taxes in such a way that they will be able to pay little or no taxes at all. They are able to do this through certain loopholes and gaps that currently exist in the system. These loopholes and gaps are seen as creating opportunities for taxpayers who are involved in cross-border activities to aggressively structure their activities to mitigate potential tax exposure or achieve no tax liabilities. They do this by exploiting; the hybrid-mismatch arrangements, shortcomings of the transfer pricing rules in jurisdictions where they operate and shifting profits from countries where their profits are made to countries with low tax rates. Consequently, some multinationals pay as little as five percent in corporate taxes, even as smaller domestic businesses pay up to 30 percent. The result of this activity is what is known as; base erosion and profit-shifting (BEPS) and it has the potential to deprive all countries of significant tax revenues. This rave debate and harsh criticism from the public influenced the intervention of the Organisation for Economic Co-operation and Development (OECD) to start its now famous BEPS Project. The OECD BEPS Project aims to provide governments or tax administrators with clear international solutions for fighting aggressive corporate tax planning strategies that artificially shift profits to locations where they are subjected to more favourable tax treatment. This paper shall address the various strands of the BEPS debate, the OECD BEPS project, the impact of the project in Africa and Nigeria. The next section shall address the various strands of the debate.